Mathias L. Pedersen & Jakob Christoffersen (eds.), Nordic Countries. Economic, Political and Social Issues (New York: Nova Science, 2012) - Joan Nymand Larsen (Nordicum-Mediterraneum, 2015)
A review of the following book: Mathias L. Pedersen & Jakob Christoffersen (eds.), Nordic Countries. Economic, Political and Social Issues (New York: Nova Science, 2012)